Stop motion as a medium to teach and learn experimental animation / Siti Hajar Aznam and Hafizah Rosli - Aznam, Siti Hajar; Rosli, Hafizah (Universiti Teknologi MARA, Kedah, 2020)
Fourth Industrial Revolution has made an impact on teaching and learning activities in the millennial era. The animation is no exception. In this context, the stop-motion techniques have been chosen to explore as part of enhancing teaching and learning experimental animation. Its required basic instrument but the outcome will be beyond the imagination. Stop-motion is one of animation technique that engages a basic technique in creating animation. This paper aims to identify the use of stop-motion in teaching and learning experimental animation in order to discover the new invention, avant-garde idea and techniques through stop motion. In this research qualitative methodology had been used. The observation process had been done with animation student within their one-semester class. The main focus on the observation was the developments of experimental animation through the stopmotion technique in three (3) stages, which is pre-production, production, and post-production. As a result of this study, the students have explored the new discoveries on the idea and techniques that they never used it before in the process of creating experimental animation. The outcome of this research will be a guideline for others who keen to learn experimental animation in the future.